Knowledge, Attitude and Coordination of Midwives in the Handling of Midwifery Complications at Labuha Health Center, 2016 - Dewi, N F; Idrus, L; Pratama, A D (KnE Social Sciences, 2018)
Minimum Service Standard (SPM) is one of the community health center (CHC or Puskesmas) performance indicators for every CHC program. In terms of handling obstetrics complications, Labuha CHC reached only 74% out of 80% targeted coverage, determined by the health Department of South Halmahera District, in 2013. This research aims at knowing the picture of individual, psychological and organizational variables, that is, knowledge, skill, attitude and coordination of CHC midwives in handling obstetrics complications in accordance with SPM at Labuha CHC, Bacan Sub-district of South Halmahera District in 2016. The study was done through a qualitative method of in-depth interview. This research studied the following: (1) Individual variables, namely, midwife’s knowledge and skill, (2) Psychological variables, that is, midwife’s attitude, and (3) Organizational variables, which was the coordination of midwives in handling obstetrics cases at CHC level. This study suggested that the midwives were well-trained in handling obstetrics cases with complication. Better supervision and coordination by midwives coordinator were very important aspects to make sure that the midwives worked in accordance with their duties and responsibilities. It was expected that efforts could improve the attitudes, and the compliance, so as to achieve better performance and the achievement of SPM indicators. The study also suggested that in addition to the aforementioned individual, psychological and organizational variables, future study would be more focused on higher level of organizational variables, that have not been explored in this study, namely at district or provincial levels. Keywords: midwife, Minimum Service Standard (SPM), knowledge, attitude, compliance